Synthesis, Characterization, and Biological Activity of Mixed ligand Complexes from 8-Hydroxyquinoline and new Ligand for β-Enaminone - Maysam B. Abdulsalam, Ahmed T. Numan, (Pakistan Journal of Medical & Health Sciences, 2022)
The synthesized ligand [4-chloro-5-(N-(5,5-dimethyl-3-oxocyclohex-1-en-1-yl)sulfamoyl)-2-((furan-2-ylmethyl)amino)benzoic acid] (H2L1) was identified utilizing Fourier transform infrared spectroscopy (FT-IR), 1 H, 13 C – NMR, (C.H.N), Mass spectra, UV-Vis methods based on spectroscopy. To detect mixed ligand complexes, analytical and spectroscopic approaches such as micro-analysis, conductance, UV-Visible, magnetic susceptibility, and FT-IR spectra were utilized. Its mixed ligand complexes [M(L1)(Q)Cl2] [ where M= Co(II), Ni(II), and Cd(II)] and complexes [Pd(L1)(Q)] and [Pt(L1)(Q)Cl2]; [H2L1] =β-enaminone ligand =L1 and Q= 8-Hydroxyquinoline = L2]. The results showed that the complexes were synthesised utilizing the molar ratio M: L1:L2 (1 :1 :1). The formation of six-coordinate octahedral geometry was proposed for metal complexes Co (II), Ni (II), Cd (II), and Pt (IIII), while the Pd (II) complex was square planar. By using the agar well diffusion method, the ligands and complexes were evaluated for antibacterial activity against Staphylococcus aureus, Escherichia coli. The studies demonstrate that the ligand and its complexes have variable activity against the bacterial types, Some of the complexes had an effect on bacteria, while others had less inhibitory action than the ligand. Also, the produced ligand and its metal complexes have been tested for fungi (Candida albicans );the complexes exhibited suppressing activity against fungi compared to the ligand prepared from them. Keywords: β-enaminones, 5,5-dimethylcyclohexane-1,3-dione , Furosemide, Mixed-ligand complexes, 8-Hydroxyquinoline.